Abjection, Remembering and the Still-Performing Document. - Vivash, Kelsy (Performance Research, 2014)
In the same way that Kristeva describes how abject substances gesture towards the dissolution of the subject and, thereby, towards death, it will be my contention that the still-performing documents created during the performances of Mendieta and Antoni embody abjection – at least in part – by aestheticizing the replacement of the departed subject with the objects that once surrounded it.